Realtime Covid19 Tracker Using React (International Journal of Innovative Research in Computer Science & Technology, 2020)
Analysing the data of a deadly pandemic  that has created a mess in this wonderful world and  caused a lot of deaths is a need of this hour such that we  can easily take preventive measures and hold this  pandemic growth and eradicate it with certain measures  and proper planning and a study is needed to analyse  whether any inter-mediate hosts have facilitated the  transmission of the virus to humans or vice versa and this  could only be done if precise data is analysed [1][6]. The main objective behind writing this paper is to present an  idea that how knowledge to an emerging frontend  technology like React JS can lead to a wonderful user  interface that can serve as a data analyser web software  for this deadly pandemic. The paper revolves around a  project created with a bunch of features of React JS from  exciting frontend components with Material UI to writing  CSS, JSX and making API calls to collect worldwide data  related to Corona virus [9]. The major highlights of the project entitled in this paper are no page reloads,  Responsiveness, body-parsing, API calls for data  collection, JSX (HTML inside JS), sorting algorithms,  dynamic data representation, REDUX, data representation  in dynamic graphs/pie charts. In this a large number of  npm packages like react, react-dom, @material-ui etc  along with React JS and CSS library like Material UI has  been used in order to code the website such that it results  in an attractive, responsive and a beautiful project with a  single technology that is JS. The web software entitled in  this paper is a complete package of features of React JS  integrated with some other frontend technologies like  CSS and material UI going through which any user can  analyse the data related to corona virus geographically as  well as graphically.
Keywords: Dynamic data representation; Responsiveness; API calls; JSX; Sorting algorithms; NPM packages; Page reloads; JSON; Library; components